Stress-strain state of beam corrugated web under patch loading - Semchuk, I. Y.; Nilova, T. O. (КНУБА, 2019)
It’s presented results of numerical investigation via the finite elements method (FEM) of stress-strain state of beam corrugated web under local load action in its plane. It’s concluded that the values of local normal stresses at the level of the web and the flange connection are directly dependent on the web thickness, the flexural and the longitudinal rigidity of the flanges and virtually don’t depend on the web height. A practical technique for determining the limit values of local normal stresses in the web and its stress-strain state is developed.
Keywords: corrugated web; stress-strain state; strength condition; patch loading; the department steel and wooden constructions; 624.071.3.014